The future of endoscopy: Advances in endoscopic image innovations. Issue 4 (22nd August 2019) - Gulati, Shraddha; Patel, Mehul; Emmanuel, Andrew; Haji, Amyn; Hayee, Bu'Hussain; Neumann, Helmut
Abstract : The latest state of the art technological innovations have led to a palpable progression in endoscopic imaging and may facilitate standardisation of practice. One of the most rapidly evolving modalities is artificial intelligence with recent studies providing real‐time diagnoses and encouraging results in the first randomised trials to conventional endoscopic imaging. Advances in functional hypoxia imaging offer novel opportunities to be used to detect neoplasia and the assessment of colitis. Three‐dimensional volumetric imaging provides spatial information and has shown promise in the increased detection of small polyps. Studies to date of self‐propelling colonoscopes demonstrate an increased caecal intubation rate and possibly offer patients a more comfortable procedure. Further development in robotic technology has introduced ex vivo automated locomotor upper gastrointestinal and small bowel capsule devices. Eye‐tracking has the potential to revolutionise endoscopic training through the identification of differences in experts and non‐expert endoscopist as trainable parameters. In this review, we discuss the latest innovations of all these technologies and provide perspective into the exciting future of diagnostic luminal endoscopy.